A review on acceptability of denture polymers having gold and silver nanoparticles - Eswaran, M. A.; Abraham A, Ponsekar; Afritha , A.; Lubnaz, S.; Rathee, Suprabha; Ranjani, T (International Journal of Dental Materials, 2022)
In dentistry, polymethyl methacrylate (PMMA) is commonly used as a base material for dentures. PMMA has been widely used in a range of dental applications because of its specific features, including its low density, aesthetics, cost-effectiveness, ease of manipulation, and flexible physical and mechanical characteristics. Despite having many advantageous qualities, it has a lot of cons like weak flexural strength, poor wear resistance, polymerization shrinkage, and poor durability etc., The emergence of nanotechnology has allowed for the improvement of the aforementioned drawbacks through the use of different nanoparticles. Silver nanoparticles have been used in dentistry due to their antimicrobial, and antifungal properties. They also enhance the mechanical properties of materials leading to improved outcomes. Gold nanoparticles are available in different sizes and concentrations to exhibit their beneficial outcomes. This review aimed to discuss the properties of silver and gold nanoparticles, their form of incorporation, benefits, acceptance and their clinical significance when added with denture polymers.